“Kyprei” and “kalamarades”: Νegotiations of Greek hegemony from the margins of the Greek-speaking world - Karathanasis, Pafsanias (The Greek Review of Social Research, 2023)
Based on ethnographic research carried out in Greece and Cyprus in the period 2020-2021, the article concerns the relations between the two countries and their citizens. Inspired by recent changes in the two countries, and specifically by the new Greek migration of the crisis, I explore contemporary negotiations and transformations that take place both at the official level of relations between the two countries, and in the everyday life of their citizens. In particular, the article explores issues of familiarity, cultural distance and cultural hegemony, as they appear between the crypto-colonial Greek and the post-colonial Cypriot context and are transformed in the periphery of the Greek-speaking world.